Soil macrofauna as bioindicator of the recovery of degraded cerrado soil - Kitamura, Aline Emy [UNESP]; Tavares, Rose Luiza Moraes; Alves, Marlene Cristina [UNESP]; de Souza, Zigomar Menezes; Siqueira, Diego Silva (FapUNIFESP (SciELO), 2020)
The construction of the hydroelectric power plant of Ilha Solteira, in state of São Paulo, was initiated in the 1960s, when an average, 8.60 m of soil depth was removed, resulting in a degraded area. A plan for the recovery of the area started in 2005 in Selvíria / MS with the use of plant species adapted to the Cerrado biome. This study aimed to evaluate the soil macrofauna of an area under recovery by using different types of soil cover (1-bare soil (control); 2-native Cerrado vegetation; 3-specie Astronium fraxinifolium; 4-Astronium fraxinifolium + Canavalia ensiformis; 5-Astronium fraxinifolium + Raphanus sativus; 6-Astronium fraxinifolium + Brachiaria decumbens + sewage sludge). Soil macrofauna was evaluated in 2005, 2006 and 2007 using the direct collection method and manual counting. Number of species, diversity and uniformity index were determined. Principal component analysis (PCA) and cluster analysis were used for data interpretation. Results showed that treatment 6 (Astronium fraxinifolium+ Brachiaria decumbens+ sewage sludge) increased the soil macrofauna population by approximately 4 to 6 times more than the other types of cover after three years of evaluation. And the PCA and cluster analysis showed the approximation of the data between treatment 6 and Cerrado, which represents the most appropriate treatment for the recovery of the degraded soil.
Macrofauna do solo como bio indicador da recuperação de um solo degradado de cerrado
Keywords: Bioindicators; Cluster analysis; Principal component analysis; Uniformity